An Implementation Framework for Telemedicine to Address Noncommunicable Diseases in Thailand. (November 2021) - Chattranukulchai, Pairoj; Thongtang, Nuntakorn; Ophascharoensuk, Vuddhidej; Muengtaweepongsa, Sombat; Angkurawaranon, Chaisiri; Chalom, Kittiphan; Supungul, Somruethai; Thammatacharee, Jadej; Kittikhun, Suneerat; Shantavasinkul, Prapimporn Ch; Leelahavarong, Pattara; Rawdaree, Petch; et al.
To maintain the continuity of noncommunicable disease (NCD) services and ascertain the health outcomes of patients with NCDs during the COVID-19 (coronavirus disease 2019) outbreak in Thailand, various telemedicine services have been developed. To achieve this determination, the implementation framework has been constructed based on recommendations from multidisciplinary experts (Thai NCD Collaboration Group). Within the framework, all key elements are illustrated with their priority and expected collaborations. Ultimately, active collaborations from multi-stakeholders are vitally important to ensure that telemedicine services for NCDs will finally become practical, successful, and sustainable.